I like me! - Carlson, Nancy L. (New York Puffin Books, 1988)
By admiring her finer points and showing that she can take care of herself and have fun even when there$1 (Bs no one else around, a charming pig proves the best friend you can have is yourself.s
Keywords: Pigs -- Fiction; Self-reliance -- Fiction